Burkholderia gut symbiont modulates titer of specific juvenile hormone in the bean bug Riptortus pedestris. (October 2019) - Lee, Junbeom; Kim, Chan-Hee; Jang, Ho Am; Kim, Jiyeun Kate; Kotaki, Toyomi; Shinoda, Tetsuro; Shinada, Tetsuro; Yoo, Jin-Wook; Lee, Bok Luel
Abstract: Recent studies have provided molecular evidence that gut symbiotic bacteria modulate host insect development, fitness and reproduction. However, the molecular mechanisms through which gut symbionts regulate these aspects of host physiology remain elusive. To address these questions, we prepared two different Riptortus-Burkholderia insect models, Burkholderia gut symbiont-colonized (Sym) Riptortus pedestris insects and gut symbiont-noncolonized (Apo) insects. Upon LC-MS analyses, juvenile hormone III skipped bisepoxide (JHSB3 ) was newly identified from Riptortus Apo- and Sym-female and male adults' insect hemolymph and JHSB3 titer in the Apo- and Sym-female insects were measured because JH is important for regulating reproduction in adult insects. The JHSB3 titer in the Sym-females were consistently higher compared to those of Apo-females. Since previous studies reported that Riptortus hexamerin-α and vitellogenin proteins were upregulated by the topical abdominal application of a JH-analog, chemically synthesized JHSB3 was administered to Apo-females. As expected, the hexamerin-α and vitellogenin proteins were dramatically increased in the hemolymph of JHSB3 -treated Apo-females, resulting in increased egg production compared to that in Sym-females. Taken together, these results demonstrate that colonization of Burkholderia gut symbiont in the host insect stimulates biosynthesis of the heteroptera-specific JHSB3, leading to larger number of eggs produced and enhanced fitness in Riptortus host insects. Highlights: Heteroptera-specific JHSB3 is a bona fide juvenile hormone in R. pedestris insect. The Burkholderia gut symbiont modulates titter of JHSB3 in Riptortus female insect. The expression of hemolymph proteins are induced by topical application of JHSB3 . This study describes molecular relationship between gut-symbiont and host juvenile hormone.